Penegakan Hukum dan Ketertiban Masyarakat: Kajian Yuridis Empiris Peran dan Komunikasi Kepolisian di Kota Bandung - Zeevano Albariq Baskara; Arman Lany; Naditha Rizkya Hantoro (Universitas Medan Area, 2026)
Public order in urban areas shows dynamics that require attention in an effort to maintain social order, especially related to the role of the police in the city of Bandung as an institution that interacts directly with the community. This study aims to analyze the role of the police in law enforcement against public order by examining the suitability between legal norms and practices in the field. The problem is focused on the implementation of law enforcement and the process of forming community compliance in daily social life, including through interaction and communication between the apparatus and the community. In order to approach this problem, a reference to legal system theory is used which emphasizes the relationship between the substance of the law, the structure of law enforcement, and the legal culture of the community. Data were collected through semi-structured interviews with police officers and the public, limited observations in public spaces, and literature studies of laws and regulations and journal articles, then analyzed qualitatively using an empirical juridical approach. The results of the study show that the enforcement of order has taken place through supervision, regulation, and control activities, and accompanied by efforts to coach the community. This study concludes that law enforcement in maintaining order needs to be understood as a sustainable process that prioritizes a balance between the implementation of rules, fostering legal awareness, and community involvement. This research contributes by showing that interaction between the apparatus and the community is an important part in understanding the relationship between legal norms and social practices.